2008
DOI: 10.1002/j.2050-0416.2008.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Main Degradation Products of Patulin Generated Through Heat Detoxication Treatments

Abstract: The chemical stability of patulin (PAT) was studied in model aqueous media at different temperatures and pH values in the presence and absence of sulfites. At pH 6, 50% was degraded within one hour at 100°C. At lower pH the detoxication efficiency was strongly reduced. The compound 3-keto-5-hydroxypentanal was shown to be the main degradation product of patulin. As the hemiacetal function has to be transformed into an aldehyde before retroaldolization and lactone hydrolysis, sulfites, as expected, improved det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 12 publications
1
25
0
1
Order By: Relevance
“…However, it is much less stable in higher pH. Collin's group has reported that 50% of patulin degrades within 1 h at 100°C in aqueous medium at pH 6 (Collin et al 2008). They have also noted that sulfites promote patulin destruction at higher pH with complete patulin degradation achieved at pH 7 within 3-h incubation at 25°C in the presence of 50 ppm SO 2 .…”
Section: Introductionmentioning
confidence: 97%
“…However, it is much less stable in higher pH. Collin's group has reported that 50% of patulin degrades within 1 h at 100°C in aqueous medium at pH 6 (Collin et al 2008). They have also noted that sulfites promote patulin destruction at higher pH with complete patulin degradation achieved at pH 7 within 3-h incubation at 25°C in the presence of 50 ppm SO 2 .…”
Section: Introductionmentioning
confidence: 97%
“…Patulin is an organic compound very soluble in water and in most organic solvents. It is stable in diluted acids and resistant to temperatures at 125ºC in the 3.5 -5.5 pH range (Collin et al, 2008, as cited in Lovett & Peeler, 1973.…”
Section: Patulinmentioning
confidence: 88%
“…This method can be easily implementable, is high-throughput and cost-effective. It offers simultaneous UV pasteurization of juices and reduction of PAT without severe alterations in the final product [89].…”
Section: Patulinmentioning
confidence: 99%